Application of Neo Vernacular Architecture in The Java Traditional Building Gallery Building in Surabaya - Irfani, Muhammad Syihabuddin; Widjajanti, Wiwik Widyo (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
The application of local values into a modern object is the general definition of Neo Vernacular Architecture. The relationship between building design and clothing has a style that is based on the times, which rotates to utilise the type of design into something new. The obstacle found in the community is the lack of knowledge of the value of so much locality, one of which is in traditional bridal clothing. On the island of Java itself, bridal clothing rental or sales services only provide certain clothing objects with cultural custom themes. Therefore, it is necessary to publish the locality value of traditional bridal fashion that is not yet known to the public as an effort to preserve local culture. The purpose of planning the Javanese Traditional Bridal Fashion Gallery Centre is to advance the fashion entrepreneurship sector of the local and surrounding communities, both on a small and large scale. With this idea, it can become part of the identity of Surabaya City which can attract out-of-town visitors.